The Effect of Company Size and Macro Economy on Financial Distress - Eli Achmad Mahiri; Melia Wida Rahmayani; Ayu Gumilang Lestari (Journal of International Conference Proceedings, 2023)
The goal of this research is to identify the factors that lead to financial difficulties for businesses in the transportation sector. Many separate theoretical investigations and empirical studies on the causes of financial distress were pooled together to form the basis for this inquiry. This research strategy takes a causal associational tack. Purposive sampling was used to select 16 transportation-related companies trading on the Indonesia Stock Exchange during the study's time period (2019-2021). Logistic regression using SPSS 25 is the method used for analysis. Financial difficulty was found to be related solely to the size of the company. Meanwhile, inflation and currency rates, both macroeconomic variables, have little effects on financial distress. In order for it to serve as a cohesive role model, we suggest that future research on financial distress through firm size, which is a component of financial and macroeconomic ratios, be prioritized. Most of the previous research only used the variable financial ratios as a whole and no one has detailed them yet. However, the focus of the significance of our research is on the comprehensive and overall description of these aspects as well as the details of the drivers of financial distress.